Analysis of similarity and discrepancy of response of linear system to etalon signal by the instrumentality of double normal transformation (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2010)
Methodology of distortion estimation of input signal with dispersion of component values by the instrumentality of double normal transformation was demonstrated.